2017
DOI: 10.1124/mol.116.107003
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of Human Pregnane X Receptor by MicroRNA-18a-5p: Evidence for Suppression of MicroRNA-18a-5p Expression by Rifampin and Rilpivirine

Abstract: Small noncoding microRNAs act as post-transcriptional regulators of gene expression involved in diverse biologic functions. Pregnane X receptor (PXR, NR1I2), a member of the superfamily of nuclear receptors, is a transcription factor governing the transport and biotransformation of various drugs and other chemicals. In the present study, we identified a specific microRNA (miR) involved in regulating the expression and functionality of human PXR (hPXR). According to bioinformatics analysis employing three commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“… 65 , 66 Following on from the paper by Sharma et al that concluded that miR-18a-5p is a negative regulator and research by Vachirayonstien et al that stated that miR-30c-1-3p could be a suppressor of PXR, our results extend the knowledge of miRs on the PXR signaling pathway. 67 , 68 …”
Section: Discussionmentioning
confidence: 99%
“… 65 , 66 Following on from the paper by Sharma et al that concluded that miR-18a-5p is a negative regulator and research by Vachirayonstien et al that stated that miR-30c-1-3p could be a suppressor of PXR, our results extend the knowledge of miRs on the PXR signaling pathway. 67 , 68 …”
Section: Discussionmentioning
confidence: 99%
“…In human and mouse liver cells, Smutny et al observed a significant upregulation of miRNA-18a-5p expression following 6h of incubation with the PXR ligands rifampicin and PCN, suggesting a negative feedback regulation in hepatic cells [131]. In contrast, Sharma et al reported that miRNA-18a-5p is inhibited in LS180 colon adenocarcinoma cells incubated with rifampicin for 6h [166]. These results highlight the tissue-specific regulation and the importance of temporal profiling.…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…miR-30c-1-3p is identified as a PXR silencer, thus decreases the mRNA levels of PXR and alters CYP3A4 expression [33]. Other post-translational PXR regulators are miR-18a-5p, miR-148a, miR-34a, miR-150, miR-27a and miR-140-3p, which negatively regulate PXR expression, resulting in decreased CYP3A4 expression [34][35][36][37][38]. miR-449a is described to inhibit PXR through HNF4-a in human hepatocytes [39].…”
Section: Post-translational and Post-transcriptional Pxr Modificationsmentioning
confidence: 99%